Habitos y costumbres alimentarias de los estudiantes de la carrera de nutrición y gastronomía de la universidad Le Cordon Bleu Perú - Támara T., Stalein Jackson (2014)
In the present research of body mass index (BMI) were measured and food habits and practices of students in the careers of Nutrition and Food, University Le Cordon Bleu Peru met. It’s main objective was to make a comparison between food life style of students to do two samples of 12 students took career Kolmogorov and were applied to determine whether the distributions are normal in the samples, the test was applied Pearson to determine the correlation between variables and finally the Chi square and Spearman wereapplied to measure the independent variables were the final results no relationship between the lifestyles of students of both races but there is a tendency students have better nutrition food habit and habit that students cuisine.